Switching Between Methanol Accumulation and Cell Growth by Expression Control of Methanol Dehydrogenase in Methylosinus trichosporium OB3b Mutant - Ito, Hidehiro; Yoshimori, Kosei; Ishikawa, Masahito; Hori, Katsutoshi; Kamachi, Toshiaki (Frontiers in Microbiology, 2021)
Methanotrophs have been used to convert methane to methanol at ambient temperature and pressure. In order to accumulate methanol using methanotrophs, methanol dehydrogenase (MDH) must be downregulated as it consumes methanol. Here, we describe a methanol production system wherein MDH expression is controlled by using methanotroph mutants. We obtained the MxaF knockout mutant of Methylosinus trichosporium OB3b by referring to the methods of previous studies. It could only grow with MDH (XoxF) which has a cerium ion in its active site and is only expressed by bacteria in media containing cerium ions. In the presence of 0 μM copper ion and 25 μM cerium ion, the mutant grew normally. Under conditions conducive to methanol production (10 μM copper ion and 0 μM cerium ion), cell growth was inhibited and methanol accumulated. The aforementioned conditions were repeatedly alternated by modulating the metal ion composition of the bacterial growth medium.